2009
DOI: 10.1056/nejmoa0810699
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib or Carboplatin–Paclitaxel in Pulmonary Adenocarcinoma

Abstract: Gefitinib is superior to carboplatin-paclitaxel as an initial treatment for pulmonary adenocarcinoma among nonsmokers or former light smokers in East Asia. The presence in the tumor of a mutation of the EGFR gene is a strong predictor of a better outcome with gefitinib. (ClinicalTrials.gov number, NCT00322452.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

153
5,795
32
150

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 7,354 publications
(6,232 citation statements)
references
References 29 publications
153
5,795
32
150
Order By: Relevance
“…Molecular therapy has become a newly emerging regimen over the last decade 4. With lesser toxicity, patients with sensitive molecular alterations could benefit more from an inhibitor therapy than traditional chemotherapy 5, 6, 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular therapy has become a newly emerging regimen over the last decade 4. With lesser toxicity, patients with sensitive molecular alterations could benefit more from an inhibitor therapy than traditional chemotherapy 5, 6, 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…5,28,29,[37][38][39] Recent studies have provided more compelling evidence of the clinical benefits of anti-EGFR treatment in the appropriate setting. 13,15,22,38,[40][41][42][43][44][45][46][47][48] Evidence from the large phase III randomized Iressa Pan-Asia Study trial and other phase III trials have prompted the American Society of Clinical Oncology to issue a provisional clinical opinion recommending the testing of EGFR mutational status in patients being considered for first line EGFR TKI therapy owing to their demonstrated benefit on progression-free survival. 22,41 Of note, they caution that no definitive benefit has been shown in patients treated with first-line TKIs in regards to overall survival.…”
mentioning
confidence: 99%
“…In 2005, the Food and Drug Administration (FDA) restricted gefitinib from being used to treat all patients with NSCLC [44]. Subsequent trial evidence revealed heterogeneity in response to gefitinib that was unobserved previously, with respect to EGFR-TK mutation status [45]. The FDA and European Medicines Agency, consequently, granted marketing authorization for gefitinib in patients with NSCLC that had activating mutations of EGFR-TK [46].…”
Section: The Economic Case: In Practicementioning
confidence: 99%